Morphology Matters, but What Do Teacher Candidates Know About It?. (August 2019) - Washburn, Erin K.; Mulcahy, Candace A.
Skilled reading is a complex process in which many subskills are involved, including an awareness of the morphological structure of language. Morphological awareness is the ability to understand how words are broken into meaningful units (e.g., affixes, root words). Explicit and systematic teaching of morphological concepts are reported to help striving readers, particularly those in upper elementary, middle, and secondary grades, with reading. To teach morphological concepts and their relation to reading, teachers need to have both awareness and knowledge of morphology. In the present study, general and special education teachers' knowledge of morphological concepts are examined. Results indicate that teachers, regardless of type of certification (general vs. special education) or grade level (elementary vs. secondary), have difficulty identifying morphemes in both simple and complex words. Suggestions for what and how teacher educators can integrate the teaching of morphological concepts into teacher preparation contexts are provided.